Fashion and clothing instrument for Malaysian fashion lecturers: an analysis of the instructors’ competency scale - Arasinah Kamis,; Suriani Mohamed,; Zaliza Hanapi,; Che Ghani Che Kob,; Rahimah Jamaluddin, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
A latest fashion and clothing instrument that has high validity and reliability can serve as a predictor in measuring the competency of lecturers in the field of fashion. Indirectly, with this instrument, it is expected to improve the competency content that still needs to be explored and refined. Apart from that, this kind of exploration opens up new opportunities to enrich theories and models in the fashion and clothing field. This study aims to validate the knowledge competency scale of fashion and clothing among lecturers. The questionnaires consisted of 45 items, ranging from multiple choice questions to matching questions, right and wrong questions, and fill-in-blank questions. The validation of the constructs was carried out in two phases, firstly, using the Rasch Measurement Model (RMM), and secondly using the Confirmatory Factor Analysis (CFA). Results from the RMM analysis showed that there were 18 misfit items that needed to be removed. Additionally, through the CFA (convergent and discriminant validity), the instrument recorded a consistent internal validity scales of good, acceptable, and fit to the model. All four sub-constructs were also recorded as having high validity, since the overall model showed a good and acceptable fit. In the regard, the scale was deemed successful in fulfilling the psychometric standard and the instrument was adequately stable and could be used at any given time for samples that possessed the same or almost the same criteria.